2012
DOI: 10.1007/s11064-012-0750-0
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Amyloid Beta-42, Interleukin-6 and Tumor Necrosis Factor-Alpha in Alzheimer’s Disease and Vascular Dementia

Abstract: Amyloid β42 (Aβ42) and proinflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) have been suggested to contribute to the pathogenesis of Alzheimer's disease (AD) and vascular dementia (VaD). Our aim was to examine whether the changes in these parameters would be able to discriminate the patients with AD from those with VaD and from healthy individuals. We have analyzed the levels of Aβ42, IL-6 and TNF-α in the serum of newly diagnosed 28 AD patients, 16 VaD patients and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
2
44
0
2
Order By: Relevance
“…IL-6 can be produced by lymphoid cells and macrophages in the periphery,42 43 which in turn communicates with the brain through complex transport mechanisms and cellular activation 44 45. As a result, there is local activation of the immune system in the cortex, and the microglia and astrocytes release IL-6 in the brain under Aβ deposition 46. These cells are also known to release cytokines in response to Aβ deposition.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 can be produced by lymphoid cells and macrophages in the periphery,42 43 which in turn communicates with the brain through complex transport mechanisms and cellular activation 44 45. As a result, there is local activation of the immune system in the cortex, and the microglia and astrocytes release IL-6 in the brain under Aβ deposition 46. These cells are also known to release cytokines in response to Aβ deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, proinflammatory cytokines such as TNF-α and IL-6 had also been shown as an amplifier in the amyloid cascade process [28,29]. Overproduction of IL-6 and TNF-α were related to memory impairment [30,31], which were considered a histopathological hallmark of various neurological diseases in the brain [32]. Since hippocampus is more susceptible to these cytokine-induced inflammations [33], we analyzed the mRNA and protein levels of IL-6 and TNF-α in hippocampus and found that CDT (0.81 g/kg) administration prominently inhibited the production of pro-inflammatory mediators such as IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between AD and dementia and fatty acids seem to be very complex. Many studies have found a correlation between lower PUFA levels and the risk of AD [31,32,33]. Therefore, in order to determine the role of hypercholesterolemia at various stages of triple-transgenic AD mice, in the present study the first part investigated the fatty acid profile of clams and evaluated the effects of a high cholesterol diet to inspect the heart functional changes, and the triple-transgenic AD mice were gastric-fed with Geloina eros extract (GEE), Corbicula fluminea extract (CFE) and Meretrix lusoria extract (MLE) for three months to study their effects in mechanisms to enhance-survival and anti-apoptotic effects.…”
Section: Introductionmentioning
confidence: 99%